Constructing a Knowledge-Based Database for Dermatological Integrative Medical Information. (9th December 2013) - Shin, Jeeyoung; Jo, Yunju; Bae, Hyunsu; Hong, Moochang; Shin, Minkyu; Kim, Yangseok
Abstract : Recently, overuse of steroids and immunosuppressive drugs has produced incurable dermatological health problems. Traditional medical approaches have been studied for alternative solutions. However, accessing relevant information is difficult given the differences in information for western medicine (WM) and traditional medicine (TM). Therefore, an integrated medical information infrastructure must be utilized to bridge western and traditional treatments. In this study, WM and TM information was collected based on literature searches and information from internet databases on dermatological issues. Additionally, definitions for unified terminology and disease categorization based on individual cases were generated. Also a searchable database system was established that may be a possible model system for integrating both WM and TM medical information on dermatological conditions. Such a system will yield benefits for researchers and facilitate the best possible medical solutions for patients. The DIMI is freely available online.